IMPLEMENTASI PEMBELAJARAN TERPADU DI SEKOLAH DASAR NEGERI 34 PANGKALPINANG - Muhammad Iqbal Arrosyad; Ariska; Tessa; Suryani (Universitas Muhammadiyah Bangka Belitung, 2023)
This study aims to find out the description and implementation of integrated learning in the current 34 Pangkalpinang Public Elementary School. This study uses a descriptive quantitative method using a survey. The sampling technique was total sampling, while the samples used in this study were grade 3 and 4 teachers at SD N 34 Pangkalpinang with sample collection using observation, documentation, interviews and questionnaire methods. The conclusion drawing technique is a simple descriptive analysis using the Percentage formula. Based on the results of the research, it can be stated that the implementation of integrated learning at Public Elementary School 34 Pangkalpinang has gone well, this is evidenced by the results of the research which stated that 100% (2 respondents) answered that they understood the steps for preparing an integrated learning design, 50% (1 respondent) ) answered that they really understood that integrated learning was carried out in grades 1,2 and 3, and 100% answered that they understood the steps for evaluating integrated learning with a thematic approach